Strategic implementation of integrated bioaugmentation and biostimulation for efficient mitigation of petroleum hydrocarbon pollutants from terrestrial and aquatic environment. (April 2022) - Behera, Ipsita Dipamitra; Nayak, Manoranjan; Mishra, Asmita; Meikap, Bhim Charan; Sen, Ramkrishna
Abstract: Release of petroleum hydrocarbon pollutants poses a serious problem to the terrestrial as well as marine ecosystem. This study investigated and compared the potency of different biodegradation strategies for mitigating total petroleum hydrocarbon (TPH) of petroleum refinery sludge by an integrated action of bioaugmentation and biostimulation vis-à-vis separate bioaugmentation and biostimulation approaches. The implementation of a concomitant bioaugmentation-biostimulation strategy (BABSS) involving the indigenously developed bacterial consortium and poultry litter extract showed the best performance by mitigating the TPH up to 90.3 ± 3.7% in 21 days. The GC-FID analysis confirmed the efficacy of different TPH degradation strategies. The kinetic study of TPH degradation of BABSS resulted first-order with rate 0.11 day − 1 . Thus, the BABSS proved to be more efficient in degrading TPH in an eco-friendly manner and hence, may pave the way for better management of petroleum hydrocarbon pollutants, while providing a sustainable solution to the disposal of poultry wastes. Graphical abstract: Unlabelled Image Highlights: Different biodegradation strategies were investigated for TPH degradation. Best TPH degradation was achieved by integrated bioaugmentation and biostimulation. Poultry litter extract can be used as a nutrient source for bacterial growth. The first-order model fitted much better for TPH degradation data.